Epidemiology, injury pattern and outcome of older trauma patients: A 15-year study of level-I trauma centers - Axel Benhamed; Brice Batomen; Valérie Boucher; Krishan Yadav; Éric Mercier; Chartelin Jean Isaac; Mélanie Bérubé; Francis Bernard; Jean- Marc Chauny; Lynne Moore; Marie Josée Sirois; Karim Tazarourte; et al. (PLoS ONE, 2023)
Background Older adults have become a significant portion of the trauma population. Exploring their specificities is crucial to better meet their specific needs. The primary objective was to evaluate the temporal changes in the incidence, demographic and trauma characteristics, injury pattern, in-hospital admission, complications, and outcome of older trauma patients. Methods A multicenter retrospective cohort study was conducted using the Quebec Trauma Registry. Patients aged ≥16 years admitted to one of the three adult level-I trauma centers between 2003 and 2017 were included. Descriptive analyses and trend-tests were performed to describe temporal changes. Results A total of 53,324 patients were included, and 24,822 were aged ≥65 years. The median [IQR] age increased from 57[36–77] to 67[46–82] years, and the proportion of older adults rose from 41.8% in 2003 to 54.1% in 2017. Among those, falls remain the main mechanism (84.7%-88.3%), and the proportion of severe thorax (+8.9%), head (+8.7%), and spine (+5%) injuries significantly increased over time. The proportion of severely injured older patients almost doubled (17.6%-32.3%), yet their mortality decreased (-1.0%). Their average annual bed-days consumption also increased (+15,004 and +1,437 in non-intensive care wards and ICU, respectively). Conclusions Since 2014, older adults have represented the majority of admissions in Level-I trauma centers in Québec. Their bed-days consumption has greatly increased, and their injury pattern and severity have deeply evolved, while we showed a decrease in mortality.